King Spawn. Volume 1 - Lewis, Sean Christopher; McFarlane, Todd (Image Comics, 2022)
When one of the vilest creatures ever imprisoned in Hell is released back onto Earth, Spawn follows the clues right into a trap set just for him. But why does Kincaid want Spawn to ascend the throne of Hell, and what of the prophecy of the KING SPAWN? Collects KING SPAWN #1-6.